Key Question for Literacy Co‐Teachers: What Possibilities Do We Have Together?. (2nd June 2022) - McTigue, Erin M.; Gourvennec, Aslaug Fodstad; Solheim, Oddny Judith
Abstract: Co‐teaching offers a unique opportunity space for literacy instruction; however, this opportunity is rarely optimized and the result on students' literacy growth is often unimpressive. We propose that co‐teaching is only a structural intervention, but it can become a powerful pedagogical intervention if teachers approach co‐teaching as an opportunity space to try out effective pedagogical practices that lead to student literacy growth. Studying, through mixed methods, the practices of literacy co‐teachers in early elementary, we identified important trends connected to student growth. We concluded that shared responsibility was a feature of highly effective pairs. Next, through interviews, we captured nuances of how effective dyads formed working relationships, planned together, communicated, reflected on instruction together, and organized resources. From such findings, we propose a model of change for how co‐teaching may lead to student growth—via positive co‐teaching relationships and continual shared reflection of instructional practice. Mirroring highly effective co‐teachers' approach, we provide a series of reflective co‐teaching guides to support other pairs of co‐teachers. These guides lead reading teachers throughout a school year and continually return to the essential question of: What can we do together that I cannot do alone?